Chrysin suppresses the achaete-scute complex-like1 and alters the neuroendocrine phenotype of carcinoids - Somnay, Yash R. (Cancer Gene Ther, 2015)
Carcinoids are neuroendocrine neoplasms that cause significant morbidity and mortality, and for which few effective therapies are available. Given the recent identification of the anti-cancer flavonoid chrysin, we sought to investigate its therapeutic potential in carcinoids. Here, we report chrysin’s ability to modulate the achaete-scute complex-like1 (ASCL1), a neuroendocrine-specific transcription factor highly implicated in the malignant phenotype of carcinoids and other neuroendocrine cancers. Moreover, we elucidate the role of ASCL1 in carcinoid growth and bioactivity. Treatment of two carcinoid cell lines (BON and H727) with varying chrysin concentrations suppressed cell proliferation, while reducing expression of ASCL1 and the neuroendocrine biomarker chromogranin A (CgA), demonstrated by Western blotting. Propidium iodide and PE AnnexinV/7-AAD staining and sorting following chrysin treatment revealed S/G2 phase arrest and apoptosis, respectively. This was corroborated by chrysin-induced cleavage of caspase-3 and PARP and activation of p21(Waf1/Cip1). Furthermore, direct ASCL1 knockdown with an ASCL1-specific small interfering RNA inhibited CgA and synaptophysin expression as well as carcinoid proliferation, while also reducing cyclin B1 and D1, and increasing p21(Waf1/Cip1) and p27(Kip1) expression, suggesting an arrest of the cell-cycle. Collectively, these findings warrant the deliberation of targeted ASCL1 suppression by chrysin or other agents as a therapeutic approach for carcinoid management.